PROFILE OF THE HEALTH CONDITIONS OF THE ELDERLY (Fiep Bulletin - online, 2012)
This is a qualitative research conducted with 240 elderly with the objective of characterize the health situation of elderly residents in João Pessoa, Paraiba. Data were collected from the questionnaire and analyzed using the software Excel - 2003 for construction of a database and then transferred to the SPSS (Statistical Package for Social Sciences) - version 11.0. The self-reported illnesses that have any impact to the test, ie presenting with a p less than 0.05 were: stroke, impaired vision, cardiac, hearing impeded and anemia.
Keywords: Health; Elderly; Nursing.